A critical review of the validity of the Credibility Assessment Tool (CAT) and its application to the screening of suspected malingering - Theunissen, Karen Sunette (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MOccTher)-- University of Stellenbosch, 2011.